Heat stress effects on milk yield traits and metabolites and mitigation strategies for dairy cattle breeds reared in tropical and sub-tropical countries - Habimana, Vincent; Nguluma, Athumani Shabani; Nziku, Zabron Cuthibert; Ekine-Dzivenu, Chinyere Charlotte; Morota, Gota; Mrode, Raphael; Chenyambuga, Sebastian Wilson (Frontiers in Veterinary Science, 2023)
Heat stress is a significant and challenging problem for the dairy industry worldwide due to its adverse effects on productivity and profitability. Heat stress disrupts physiological parameters, reduces milk yield and alters milk composition, and affects blood and milk metabolites in dairy cattle reared in tropical countries. Understanding the biological mechanisms of climatic adaptation, identifying candidate genes for heat tolerance, and exploring genomic diversity and signatures of selection in indicine and taurine dairy breeds can be crucial for breeding better adapted cattle in the present changing climatic conditions. Identifying sires and dams to improve heat tolerance in the tropical dairy industry in face of increasing temperatures is crucial for dairy profitability although will require availability of genetic parameters which are currently missing in many tropical countries. Estimating these parameters requires the use of random regression models (RRM) that fit reaction norms, which allow for the estimation of variance components along with continuous spectrum of environmental descriptors such as temperature humidity index (THI). This can help identify individuals that are more or less affected by environmental changes, and facilitate selection for heat tolerance in tropical environments. In this article, we reviewed the effects of heat stress on dairy cattle reared in tropical environments with regards to physiological parameters, milk yield and composition traits, milk and blood metabolites. In addition, strategies for mitigating effects of heat stress on dairy cattle in the tropics are discussed and they include physical modifications of the environment such as providing shade, and nutritional interventions. However, a cost-effective and sustainable strategy is to genetically select more adaptable and heat-tolerant breeds for use in breeding programs. This can involve using breeds such as Gir, White Fulani, or N'Dama known for their heat tolerance in crossbreeding with Holstein-Friesian or Jersey breeds. The findings of this review can contribute to policy formulations and strategies for mitigating the effects of heat stress on dairy cattle in tropical countries where the climate is hot and humid throughout the year. Key words: Heat stress, genetic models, genetic parameters, candidate genes, indicine and taurine breeds, tropical countries, and mitigation strategies